Piloting an external quality assurance program (QAP) for COVID-19 antigen rapid diagnostic tests (Ag-RDTs): findings and lessons learned from Cambodia - Vonthanak Saphonn; John Kaldor; Deborah Williamson; Sothavireak Bory; Philip Cunningham; Jessica Markby; Kennarey Seang; Jacqueline Prestedge; Chan Leakhena Phoeung; Marilyn Ninan; Kanika Heng; Andrew Valley (BMJ Open Quality)
Rapid antigen diagnostic tests (Ag-RDTs) that quickly and accurately identify SARS-CoV-2 are an essential part of the COVID-19 response, but multiple factors can affect the validity of Ag-RDTs results. In Cambodia, several commercial Ag-RDTs have become available since the COVID-19 outbreak, but quality control (QC) and external quality assurance (EQA) of these rapid tests have yet to be fully and systematically implemented. We collaborated with laboratory experts in Australia and piloted an EQA programme of the commonly used COVID-19 Ag-RDTs at the University of Health Sciences’ MERIEUX Laboratory (Tier 1 site—responsible for the in-country receipt and distribution of QA material) and four other participating laboratories (Tier 2—healthcare facility based) between November 2021 and November 2022. The preimplementation training including the Khmer-translated documentation was conducted virtually for Tier 1 laboratories and in-person for Tier 2 laboratories. All QC (n=290) and EQA (n=60) specimens were distributed to the laboratories and testing was performed according to the frequency of Ag-RDTs use in each laboratory. All National Reference Laboratory-provided EQA and QC specimens were tested and results were submitted via the EDCNet portal using QR code scanning. The Tier 1 laboratory reported 100% concordance with the EQA reference result, while some of Tier 2 laboratories’ results were discordant. While continued capacity building and support with troubleshooting have been key to the successful EQA piloting at the UHS laboratory, the programme experienced delays in the shipping/delivery of EQA and QC panels due to customs and border requirements, which could have hindered implementation and potentially impacted the quality of the QA materials. The pilot EQA programme demonstrated potential scalability and provided data on the reliability of test results at the site. However, to ensure sustainability and practicability of this activity, in-country EQA panel preparation may need to be considered.